PENDIDIKAN DALAM PERSPEKTIF AL-QURAN - Subhan, Mohammad (STAIN Pamekasan, 2010)
Abstract : When mankind is born, they have been endowed with the basic skills, physical and spiritual which will be developed through education. Without education, these potentials cannot develop optimally. Thus, education is conditio sine quanon to develop human potentials to create human beings who are ready to serve God, becoming caliph on Gods mandate, and to realize the joy of living in the world and the hereafter. To achieve these objectives, the development of human potentials through education must be based on quranic values.